THE RELATIONSHIP BETWEEN THE ACTIVITY OF THE SYMPATHETIC-ADRENALINE SYSTEM AND IMMUNE STATUS IN PATIENTS WITH MYOCARDIAL INFARCTION - Kodirova G.I. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Ischemic heart disease (IHD), especially the acute form of myocardial infarction (MI), has acquired in recent years not only important medical but also social significance due to the increase in morbidity, high mortality, and loss of working capacity at various ages and professions [1]. Literary sources of recent years indicate that in order to understand the development of coronary heart disease, it is necessary to further study the systems of blood circulation regulation, in particular the sympathetic-adrenal system (SAS) [ 2,10]. Changes in the activity of the SAS are of significant importance in the pathogenesis of coronary heart disease.